THE EFFECT OF COOPERATIVE LEARNING TOWARDS STUDENTS LEARNING ACHIEVEMENT OF ENGLISH COURSE 1 AT STIT AL URWATUL WUTSQO JOMBANG - Khudriyah, Khudriyah (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2018)
Teaching English in private college needs hard effort to reach the learning goal, because most of students are not interested in English. That is why the instructors have to make effort to be succeed in the teaching and learning process. This research is quantitative research using two- way anova as analysis. This research purpose is to know whether or not the cooperative learning models effective to teach English course 1. The result are: from three classes and three learning models there is one class who has low learning achievement after treating by three learning models. The students English Course 1 score based on classes interaction and treatments are equal. Based on the treatment given, there is equal of studentâs English course 1 score who had treated by debate and role play or role play and game as model. However, it is significance difference of studentâs English course 1 score who had given debate and game as model. It means that cooperative learning is effective to teach English course 1 in STIT al Urwatul Wutsqo.